The Return of Media Diplomacy: Examples from Kosovo - Hasan Saliu; Gazmend Abrashi (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
After the Cold War, states focused their campaigns on self‐promotion on the global stage, so media diplomacy has been pushed to the periphery, hence not being a central research theme. However, the geopolitical clashes over Kosovo and the war in Ukraine have repositioned the role of media diplomacy in international politics. This paper aims to analyze Kosovo's media diplomacy in the following key moments: at the time of the declaration of independence (2008), and during the Russian aggression in Ukraine (2022). Data were collected from global media such as CNN, Al Jazeera, Reuters, and The New York Times, which have given space to Kosovo’s political actors and influential global politicians. The US president Bush was the example of the enormous media coverage in 2008. Messages of these communications were analyzed using the framing method. The results show that media diplomacy revived in three cases: before and after Kosovo's declaration of independence in 2008, and again in 2022, with the fear that the Russian scenario for Ukraine would be followed by Serbia against Kosovo. Also, media diplomacy today establishes communications between countries with no diplomatic relations and even between countries with strained relationships.